Subungual Osteochondromas of the Toe: Two Case Reports for Diagnosis and Treatment - Lee, Myung Chul; Seo, Chan Eol; Kim, Wook Youn; Kim, Wan Seop; Kim, Jeenam; Shin, Donghyeok; Choi, Hyungon (Archives of Plastic Surgery, 2023)
Benign cartilaginous tumors, known as chondrogenic tumors, show cartilage components in the microscopic diagnosis. We present two clinical cases with cartilaginous tumors of the toes showing distinctive clinical manifestations. Two juvenile patients visited our outpatient clinic due to tumors with toenail deformities. A 10-year-old girl presented with a palpable mass with a nail deformity on the left third toe. The initial pathology report was soft tissue chondroma until complete resection. Another 15-year-old male patient visited the dermatology department with a toenail deformity and underwent a punch biopsy. The pathology report was fibrosis with myxoid degeneration. Excisional biopsies were performed for both patients. In the operative field, we observed exophytic tumors connected to the distal phalangeal bones. The final pathology reports were subungual osteochondroma on both patients. The specimen exhibited mature bone trabeculae with a focal cartilaginous cap. Benign cartilaginous tumors have a slow, progressive course and do not show significant symptoms. However, tumors in subungual areas are accompanied by toenail deformities and they can cause pain. Their clinical characteristics lead to a delayed diagnosis. Surgeons can be confused between soft tissue and chondrogenic tumors. When they conduct physical examinations, these categories should be considered in the differential diagnosis.
Keywords: osteochondroma; toe